2010
DOI: 10.1016/j.neuroimage.2009.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Independent component analysis reveals dynamic ictal BOLD responses in EEG-fMRI data from focal epilepsy patients

Abstract: Introduction-Seizures occur rarely during EEG-fMRI acquisitions of epilepsy patients, but can potentially offer a better estimation of the epileptogenic zone than interictal activity. Independent component analysis (ICA) is a data-driven method that imposes minimal constraints on the hemodynamic response function (HRF). In particular, the investigation of HRFs with clear peaks, but varying latency, may be used to differentiate the ictal focus from propagated activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 69 publications
4
52
0
Order By: Relevance
“…Our findings of ICs spatially concordant with the seizure onset zone, complement a recent study in which spatially concordant ICs were identified in patients in whom a GLM analysis had previously revealed seizure-related changes (Levan et al, 2010) . We have extended the ICA approach by applying it to all cases regardless of the GLM approach and used the gold standard of icEEG for validation rather than the HRF.…”
Section: Icasupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings of ICs spatially concordant with the seizure onset zone, complement a recent study in which spatially concordant ICs were identified in patients in whom a GLM analysis had previously revealed seizure-related changes (Levan et al, 2010) . We have extended the ICA approach by applying it to all cases regardless of the GLM approach and used the gold standard of icEEG for validation rather than the HRF.…”
Section: Icasupporting
confidence: 89%
“…We expected to find "BOLD" components with a spatial pattern involving sub-cortical structures, (Federico et al, 2005;Levan et al, 2010;Tyvaert et al, 2008), but none were observed. This may be because the classifier was trained for the cortex and sub-cortical components are generally smaller in size, so the degree of clustering on which ICA depends may not be comparable (Formisano, 2009).…”
Section: Independent Component Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…Having both fairly high spatial and temporal resolu- analysis [68][69][70] , graph theory [61,62] , and dynamic causal modeling [64] . Applications of these methods to epilepsy need close collaboration among multi-disciplinary investigators, especially when multiple techniques (e.g., structural MRI, diffusion MRI, EEG, as well as fMRI) are required.…”
Section: Discussionmentioning
confidence: 99%